2011
DOI: 10.1080/15363831003782882
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Quantitative Structural Relationships of the Electron Transfer and Electrochemical Properties ofCis-Unsaturated Thiocrown Ethers and Supramolecular Complexes [X-UT-Y]@[La2@C72(Adamantylidene Mono-Adducts)n] (n=0,1)

Abstract: Endohedral fullerenes belong to a new class of compounds that are technologically and scientifically important owing to their unique structures and optoelectronic properties. The isolated pentagon rule (IPR) states that all pentagonal carbon rings are isolated in the most stable fullerene. Metallofullerenes M@C n , are a class of spherical carbon allotrope group with unique properties. Electron transfer between metallofullerenes and other molecules is thought to involve the transfer of electrons between molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
(172 reference statements)
0
4
0
Order By: Relevance
“…The ratio of the sum of the number of carbon atoms (n c ) and the number of sulfur atoms (n s ) to the product of these two numbers (μ cs ) is a useful numerical and structural value for the unsaturated thiocrown ethers 1-9 that were investigated (78,79,(89)(90)(91)(92)(93).…”
Section: Graphing and Mathematical Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ratio of the sum of the number of carbon atoms (n c ) and the number of sulfur atoms (n s ) to the product of these two numbers (μ cs ) is a useful numerical and structural value for the unsaturated thiocrown ethers 1-9 that were investigated (78,79,(89)(90)(91)(92)(93).…”
Section: Graphing and Mathematical Methodsmentioning
confidence: 99%
“…The use of effective mathematical methods in making strong correlations between chemical properties and the indices have been reported (83)(84)(85)(86)(87)(88)(89)(90), which is an important area of development. μ cs has defined by the ratio of the sum of the number of carbon atoms (n c ) and the number of sulfur atoms (n s ) with the product of these two items for 1-9 (89)(90)(91)(92)(93). This index was a useful numerical and structural value in the studies reported here on the unsaturated thiocrown ethers 1-9.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations